Integrating Eco-Friendly Practices and Sharia Principles in Halal Tourism: A Multi-Factor Analysis of Visitor Satisfaction and Loyalty - Abdul Wahab; Zakiyah; Iman Setya Budi; Ilma Mahdiya (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2026)
The rapid growth of the global Muslim travel market has positioned halal tourism as a strategic segment of the international tourism industry. Despite this development, empirical studies integrating Muslim-friendly service quality, eco-friendly destination practices, and Sharia-based price fairness in explaining visitor satisfaction and destination loyalty remain limited. This study aims to examine the effects of Muslim-Friendly Service Quality, Eco-Friendly Destination Practices, and Sharia Price Fairness on Visitor Satisfaction and their subsequent influence on Revisit Intention and Destination Loyalty at halal tourism destinations in Banjarmasin, Indonesia. A quantitative research approach was employed using a survey of 250 tourists who had previously visited Muslim-friendly tourism destinations. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that Muslim-friendly service quality, eco-friendly destination practices, and Sharia price fairness exert positive and significant effects on visitor satisfaction. Furthermore, Muslim-friendly service quality, Sharia price fairness, and visitor satisfaction significantly enhance revisit intention and destination loyalty. Although eco-friendly destination practices do not have a significant direct effect on destination loyalty, they exert a significant indirect effect through visitor satisfaction, confirming its mediating role. These findings underscore the importance of integrating Sharia-compliant service quality, environmental sustainability, and fair pricing strategies to strengthen the competitiveness and long-term sustainability of halal tourism destinations.